Prediction of success of uterus‐preserving management in women with placenta accreta spectrum (CON‐PAS score): A multicenter international study. Issue 2 (4th March 2021) - Shazly, Sherif A.; Hortu, Ismet; Shih, Jin‐Chung; Melekoglu, Rauf; Fan, Shangrong; Ahmed, Farhat ul Ain; Karaman, Erbil; Fatkullin, Ildar; Pinto, Pedro V.; Irianti, Setyorini; Tochie, Joel Noutakdie; Abdelbadie, Amr S.; et al.
Abstract: Objective: To create a model for prediction of success of uterine‐preserving procedures in women with placenta accreta spectrum (PAS). Methods: PAS‐ID is a multicenter study that included 11 centers from 9 countries. Women with PAS, who were managed between January 1, 2010 and December 31, 2019, were retrospectively included. Data were split into model development and validation cohorts, and a prediction model was created using logistic regression. Main outcome was success of uterine preservation. Results: Out of 797 women with PAS, 587 were eligible. Uterus‐preserving procedures were successful in 469 patients (79.9%). Number of previous cesarean sections (CS) was inversely associated with management success (adjusted odds ratio [aOR] 0.02, 95% confidence interval [CI] 0.001–3.63 with five previous CS). Other variables were complete placental invasion (aOR 0.14, 95% CI 0.05–0.43), type of CS incision (aOR 0.04, 95% CI 0.01–0.25 for classical incision), compression sutures (aOR 2.48, 95% CI 1.00–6.16), accreta type (aOR 3.76, 95% CI 1.13–12.53), incising away from placenta (aOR 5.09, 95% CI 1.52–16.97), and uterine resection (aOR 102.57, 95% CI 3.97–2652.74). Conclusion: The present study provides a prediction model for success of uterine preservation, which may assist preoperative and intraoperative decisions, and promote incorporation of uterine preservation procedures in comprehensive PAS protocols. Synopsis: CON‐PAS score is a novel prediction model that may facilitate decision making and promote uterine preservation in women with placenta accreta spectrum.